Elevaç\~ao do Rio Grande (ERG): Uma análise sobre o pleito de incorporaç\~ao da ERG à plataforma continental além das 200 milhas náuticas - Jo\~ao Franswilliam Barbosa; Israel de Oliveira Andrade; Fábio Albergaria de Queiroz; Guilherme Lopes da Cunha; Taíssi Pepe de Medeiros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This discussion paper analyzes the Brazilian claim to incorporate into its continental platform beyond 200 nautical miles an area of approximately 1 million km2, called Rio Grande Rise, located approximately 800 nautical miles from the Brazilian coastline. Increasing this maritime area, Brazil must develop public policies necessary to protect, conserve and use the increased area of this maritime territory.
Keywords: K3; Q28; Q38; 330; Blue Amazon; Rio Grande Rise; United Nations Convention on the Law of the Sea (UNCLOS); South Atlantic Ocean